Demographic Antecedents of Entrepreneurial Intentions Among South African University Students - Chasaya, Wimbayi; Ayandibu, Ayansola Olatunji (iRASD Journal of Management, 2025)
Entrepreneurship literature has identified several factors influencing entrepreneurial intentions, including psychological, social, environmental and demographic. Considering the importance of youth entrepreneurship, examining how these factors affect students’ entrepreneurial inclinations is essential. Thus, the purpose of the study is to investigate the impact of age and race on the entrepreneurial inclinations of South African university students. Researchers collected data from 197 undergraduate entrepreneurship students at two public universities in Durban. Quantitative data was gathered using a self-administered structured questionnaire and analyzed using SPSS. The research found that students’ entrepreneurial intentions are not significantly influenced by age and race. This indicates that students' aspirations to initiate and manage business enterprises are unaffected by age or race. The study recommends that students should be exposed to equal entrepreneurship opportunities including education and training, support, funding and mentorship regardless of their age and race. Thus, students should be introduced to an entrepreneurial environment and ecosystem from primary school to instill in them an entrepreneurial mindset. Furthermore, entrepreneurship policies and regulatory frameworks should be developed and implemented regardless of age and race. Future research should consider the intersection between demographic factors and their influence on entrepreneurial intentions. Also, future studies can look at how demographic characteristics affect various entrepreneurship traits besides intention.